Risk Assessment of Hemodynamically Significant Arrhythmias after Elective Cardiac Operations with Cardiopulmonary Bypass Using the Modified Nomogram (Retrospective Study) - L. B. Berikashvili; M. Ya. Yadgarov; O. N. Gerasimenko; D. D. Koger; K. K. Kadantseva; V. V. Likhvantsev (Общая реаниматология)
Aim of the study was to evaluate the feasibility of using a modified nomogram (the M nomogram) to predict the occurrence of new postoperative hemodynamically significant arrhythmias after elective cardiac surgery with cardiopulmonary bypass within 30 days post operation.Materials and methods. This was a retrospective cohort study. The prognostic value of the model using ROC-analysis of the modified nomogram was estimated based on the medical records of 144 patients who underwent elective cardiac surgery with cardiopulmonary bypass.Results. The incidence of new postoperative hemodynamically significant arrhythmias was 13.9% (20 of 144 patients). For the modified nomogram, the AUC was 0.777 [95% CI: 0.661–0.892] (P<0.001); at a cutoff of 12 points, the sensitivity was 60.0% and specificity was 89.52%. The odds ratio was 10.26 (95% CI: 3.63–29.06) (P<0.001). Conclusion. The modified nomogram has an acceptable prognostic value for the occurrence of new hemodynamically significant arrhythmias after elective cardiac operations with cardiopulmonary bypass based on AUC 0.777 [0.661–0.892] (P<0.001), and is currently the best model for predicting the outcome.